The Sosialisasi Penerapan Akuakultur Dengan Pendekatan Eksositem (ADPE) di SMA Negeri 1 Lempuing Kabupaten Ogan Komering Ilir - Sofian, Sofian; Yusanti, Indah Anggraini; Jaya, Fitra Mulia; Liuhartana, Riya; Utpalasari, Rih Laksmi; Perwitasari, Lia; Sundoko, Ahmad; Indra, M.; Hidayat, Wahid (Communio: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community empowerment activities are carried out at SMA Negeri 1 Lempuing, Ogan Komering Ilir Regency, South Sumatra Province on the basis of ecosystem-based aquaculture area management which is an integrated effort between all policy stakeholders and business actors by using the ecosystem approach as a basis for increasing productivity and sustainable and efficient cultivation activities. This PKM activity is expected to have a positive impact in increasing community understanding in implementing aquaculture with an ecosystem approach. The aim of this PKM activity is to provide education and practice regarding the application of Ecosystem Approach to Aquaculture (EAA). This community empowerment activity is carried out using the public lecture method and interactive classes with a predetermined theme. The results of the PKM implementation will be evaluated regarding students' understanding of the material presented in the form of achievement of achievement indicators and benchmarks. Based on the results of the community empowerment implementation, participants were able to understand the basic thinking, definition and basic principles of EAA. Then the participants were also able to understand the detailed explanation of the principles of implementing EAA